WHAT DO SHARIAH BOARDS THINK ABOUT AI? - Nurfarahin Mohd Haridan; Hamizi Nurfarahin; Agung Sriwardhani; Nur Hani Binti Ithanin; Mohamad Azmi Nias Ahmad (Jurnal Bisnis Terapan, 2023)
This paper provides a critical discussion on the functions and capabilities of Shariah boards, considering their ultimate authority in delivering Shariah assurance to stakeholders of Islamic banks. The primary objective of this initiative is to enhance the proficiency of Islamic banking in the realm of digital finance advancement while ensuring rigorous adherence to Shariah principles. This paper discusses the significance of robo advisory in facilitating real-time Shariah counsel by Shariah boards. Additionally, it highlights the potential of blockchain management systems (BMS) in augmenting the monitoring function of Shariah boards, namely in conducting reviews and audit assessments to ensure Shariah compliance in Islamic banks.